The strategy of passenger transportation by national railway transport: The implementation of public service obligations - Butkevičius, Jonas (Transport, 2009)
Based on research carried out by the author, the article identifies the problems of passenger transportation by national railway transport such as reduction in passenger flows, the growth of transportation costs, insufficient financing of loss‐making transportation, unequal competition conditions for road transport, deficiencies of legal basis etc. Following the EU experience, passenger transportation by national railway transport is suggested to be developed. The author of the article puts forward suggestions regarding the formation of the strategy for implementing public service obligations, including the formation and implementation of public sector provisions as well as the concrete measures for railway transport.First published online: 27 Oct 2010